The Impact and Molecular Mechanisms of Exercise in Cancer Therapy - Yingjie Sun; Yixiao Ma; Lei Shi; Tong Liu; Yahong Dong; Qiguan Jin (Current Issues in Molecular Biology)
Cancer is a major global health issue, and exercise has become a key supportive treatment. It contributes to reducing cancer risk, enhancing prognosis, and aiding recovery, especially for survivors. However, the exact mechanisms, such as how exercise reduces cancer risk or enhances treatment, are still unclear. Current research often focuses on specific cancer types, ignoring the diverse needs of patients. This limits the development of personalized exercise plans. Additionally, there is insufficient comparison of exercise types—like aerobic, resistance, and high-intensity interval training—regarding their adverse effects and long-term benefits. The best combination of exercises and personalized strategies remains unknown. This review underscores the contribution of physical exercise to cancer prevention and treatment, emphasizing its positive effects on reducing fatigue, improving physical strength, and enhancing mental health. It also explores the molecular mechanisms of regulating tumor immunity and energy metabolism. Additionally, the article covers criteria for selecting exercise types and intensities, and the development of personalized exercise plans. Finally, it provides guidelines for exercise prescriptions and suggests future research directions to improve interventions for cancer patients.